3D transient multiphase model for keyhole, vapor plume, and weld pool dynamics in laser welding including the ambient pressure effect. (November 2015) - Pang, Shengyong; Chen, Xin; Zhou, Jianxin; Shao, Xinyu; Wang, Chunming
Abstract: The physical process of deep penetration laser welding involves complex, self-consistent multiphase keyhole, metallic vapor plume, and weld pool dynamics. Currently, efforts are still needed to understand these multiphase dynamics. In this paper, a novel 3D transient multiphase model capable of describing a self-consistent keyhole, metallic vapor plume in the keyhole, and weld pool dynamics in deep penetration fiber laser welding is proposed. Major physical factors of the welding process, such as recoil pressure, surface tension, Marangoni shear stress, Fresnel absorptions mechanisms, heat transfer, and fluid flow in weld pool, keyhole free surface evolutions and solid–liquid–vapor three phase transformations are coupling considered. The effect of ambient pressure in laser welding is rigorously treated using an improved recoil pressure model. The predicated weld bead dimensions, transient keyhole instability, weld pool dynamics, and vapor plume dynamics are compared with experimental and literature results, and good agreements are obtained. The predicted results are investigated by not considering the effects of the ambient pressure. It is found that by not considering the effects of ambient pressure, the average keyhole wall temperature is underestimated about 500 K; besides, the average speed of metallic vapor will be significantly overestimated. The ambient pressure is an essential physical factor for a comprehensive understanding the dynamics of deep penetration laser welding. Highlights: We report a novel 3D transient multiphase model with ambient pressure effect. Without this effect, the average keyhole wall temperature is underestimated. Without this effect, the average speed of metallic vapor is overestimated. The ambient pressure is an essential physical factor in laser welding process.